Omnichannel fulfillment strategies: defining the concept and building an agenda for future inquiry. Issue 3 (12th August 2019) - Taylor, Daniel; Brockhaus, Sebastian; Knemeyer, A. Michael; Murphy, Paul
Abstract : Purpose: Since the emergence of e-commerce uprooted traditional brick-and-mortar retail in the early 2000s, many retailers have reacted by first independently servicing both the online and in-store channels (multichannel retailing) and subsequently integrating both channels to provide a seamless front-end customer interface (omnichannel retailing). Accordingly, firms had to adjust their logistics and supply chain management (SCM) processes from fulfilling orders for each channel separately to integrating channels on the back-end (omnichannel fulfillment). This development is mirrored by an emerging stream of academic publications. The purpose of this paper is to provide a snapshot of the current state of omnichannel fulfillment research via a systematic literature review (SLR) in order to identify omnichannel fulfillment strategies and to establish an agenda for future inquiry. Design/methodology/approach: This SLR is based on 104 papers published in peer-reviewed journals through December 2018. It employs a six-step process, from research question to the presentation of the insights. Findings: All selected manuscripts are categorized based on demographics such as publication date, outlet, methodology, etc. Analysis of the manuscripts suggests that the integration of fulfillment channel inventory and resources is becoming an important objective of fulfillment management. Appropriate omnichannel strategies based on retailer attributes are not well understood. Industry specific research has been conducted necessitating generalized extension for retailers. These findings provide a clear opportunity for the academic community to take more of the lead in terms of knowledge creation by proposing paths for industry pursuit of channel integration to successfully implement omnichannel fulfillment. Opportunities for future inquiry are highlighted. Originality/value: This manuscript proposes a definition of omnichannel fulfillment strategies and identifies fulfillment links that are used interchangeably across channels as the key delimiter between omnichannel fulfillment strategies and related concepts. Six omnichannel fulfillment strategies from the extant literature are identified and conceptualized. Future research opportunities around omnichannel fulfillment, potential interdependencies between the established strategies and their impact on related SCM issues such as distribution and reverse logistics are detailed.